2020
DOI: 10.5194/adgeo-53-129-2020
|View full text |Cite
|
Sign up to set email alerts
|

Reclaiming the memory of pioneer female geologists 1800–1929

Abstract: Abstract. Female earth scientists existed in the 19th century and the beginning of the 20th century in a number exceeding what we generally imagine. In this paper I present information on 210 of them who were active from 1800 to 1929. These women often overcame great challenges to achieve their positions, sometimes only to have their work attributed to men they worked with or for. Gender discrimination made access to university difficult and access to scientific careers even harder. They found several ways to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…A less obvious bias in our work is a result of the available data records. A review of female Earth scientists (Vincent, 2020) concluded with three reasons why work by women scientists is not equitably known: (i) men took credit during their lifetimes; (ii) recognition during their lifetimes was not sustained by history for various reasons; and (iii) research on women scientists is not supported. These reasons were sometimes blatantly encountered in our search for information, such as the way in which Hertha Ayrton’s work was discredited during her time (reasons i and ii; Brandt, 2021; Jones, 2019; and references in both); less blatant examples would, by definition, be harder to detect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A less obvious bias in our work is a result of the available data records. A review of female Earth scientists (Vincent, 2020) concluded with three reasons why work by women scientists is not equitably known: (i) men took credit during their lifetimes; (ii) recognition during their lifetimes was not sustained by history for various reasons; and (iii) research on women scientists is not supported. These reasons were sometimes blatantly encountered in our search for information, such as the way in which Hertha Ayrton’s work was discredited during her time (reasons i and ii; Brandt, 2021; Jones, 2019; and references in both); less blatant examples would, by definition, be harder to detect.…”
Section: Discussionmentioning
confidence: 99%
“…Undeserved challenges to their participation notwithstanding, women have repeatedly made foundational contributions to planetary geomorphology. These contributions may go unnoticed for various reasons, as has been documented for terrestrial geologists of the 19th and early 20th centuries (Vincent, 2020). The resulting misimpression—that such individuals, if they existed at all, made only marginal contributions—has recently been shown to be incorrect in the subdisciplines of glaciology (Hulbe et al, 2010), loess studies (Fitzsimmons et al, 2018), terrestrial geomorphology (Sack, 2004) and throughout the geosciences (Vincent, 2020).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Although Gardner is mentioned as an important geoscientist of the early-mid 20th century [13,14], she has largely remained an unsung pioneer. Her travels to unknown harsh places suggest that she was an intrepid traveler, keen to see new places, mount expeditions and make discoveries on her own; her maps and publications suggest that she was a meticulous observer and documentarian.…”
Section: Introductionmentioning
confidence: 99%